2012
DOI: 10.1021/bm2017355
|View full text |Cite
|
Sign up to set email alerts
|

Effective Gene Delivery Using Stimulus-Responsive Catiomer Designed with Redox-Sensitive Disulfide and Acid-Labile Imine Linkers

Abstract: A dual stimulus-responsive mPEG-SS-PLL(15)-glutaraldehyde star (mPEG-SS-PLL(15)-star) catiomer is developed and biologically evaluated. The catiomer system combines redox-sensitive removal of an external PEG shell with acid-induced escape from the endosomal compartment. The design rationale for PEG shell removal is to augment intracellular uptake of mPEG-SS-PLL(15)-star/DNA complexes in the presence of tumor-relevant glutathione (GSH) concentration, while the acid-induced dissociation is to accelerate the rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 58 publications
4
84
0
Order By: Relevance
“…This is a match with previous literature, where it has been reported that siVEGF with non-PEG-SS-PLL vectors had low toxicity at a concentration of 200 nM. 27 The novel biodegradable PEG-SS-PLL catiomer significantly improved transfection efficiency up to 96%, markedly higher than previous studies (81.3%). 2,39 The catiomer delivered siVEGF into tumor cells more efficiently, because aggregates formed due to reductive cleavage of the intermediate disulfide bonds and resulted in the shedding of the PEG layers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is a match with previous literature, where it has been reported that siVEGF with non-PEG-SS-PLL vectors had low toxicity at a concentration of 200 nM. 27 The novel biodegradable PEG-SS-PLL catiomer significantly improved transfection efficiency up to 96%, markedly higher than previous studies (81.3%). 2,39 The catiomer delivered siVEGF into tumor cells more efficiently, because aggregates formed due to reductive cleavage of the intermediate disulfide bonds and resulted in the shedding of the PEG layers.…”
Section: Discussionsupporting
confidence: 90%
“…The protocol used to assess the stability of the PEG-SS-PLL/siVEGF complex in response to GSH has been described elsewhere. 27 GSH was added to a diluted solution of PEG-SS-PLL/siVEGF complex containing 10% FBS to reach a final concentration of 10 mM GSH. The size change of the complex was monitored by dynamic light scattering.…”
Section: Particle Size and ζ-Potential Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The buffering capacity of the copolymers was measured by acid−base titration. 6 In brief, copolymers (6 mg) were dissolved in 150 mM NaCl (30 mL) and were adjusted to pH 10 with 0.1 M NaOH. The solutions were stepwise added 0.1 M HCl (5 μL each time), and the pH values measured by a microprocessor pH meter were recorded.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…We also carried out systematic studies on PEGylated PLL [98], and PEGylated PLL combined with hydrophilic poly(l-histidine) [30] or hydrophobic poly(Lhistidine-Bzl) [50] as gene vectors. The PLL structure was optimized to enhance the biological efficacy of cleavable PEGylation.…”
Section: Cleavable Pegylated Nanovehicles In Gene Deliverymentioning
confidence: 99%